Penerapan Sistem Poin Sebagai Upaya Meningkatkan Motivasi Guru Mengajar Pada SMP Negeri 4 Kampar Kiri Hilir - Junaidi, Aspan (Komunitas Manajemen Kompetitif, 2017)
Education is a concept in building skilled and knowledgeable human resources and noble character. Teachers as the most decisive success of the educational process need to get motivation or passion in work. Work conditions that are not in accordance with the expected make the teacher decreased motivation, it is necessary to maintain the motivation in work. This research uses point system in order to maintain teacher work motivation. Using school action research methods with teachers as research objects and also through treatment per cycle and analyzed descriptively. The results showed that the assessment of teacher points system by announcing the results of the assessment and giving awards to the teacher can improve the motivation of teachers in teaching in school. Keywords: Point System, teacher motivation